New towns and the local agglomeration economy. (April 2020) - He, Sylvia Y.; Wu, Dan; Chen, Huiwei; Hou, Yuting; Ng, Mee Kam
Abstract: Ever since their first establishment in Britain in 1946, new towns have become commonplace globally as a means to accommodate spillover populations from urban areas. Many of the planned new towns have a goal of creating self-contained communities with sufficient local jobs. However, despite over seventy years of new town development, few studies have examined whether and to what extent an intra-urban agglomeration economy has formed within these towns. This paper adds to the literature on new towns' spatial planning and performance by investigating the local agglomeration economy in new towns through employment sub-centres, with Hong Kong as the study area. We identify employment centres from 2000 to 2015 to map changes in the spatio-economic structure. Our results reveal that only a few of these primary employment centres exhibit strong location agglomeration: the proportion of jobs in the long-established urban core remained stable, while the agglomeration economies in new towns have not gained much momentum in attracting a larger proportion of the city's total employment. The new towns' sub-centres also indicate a similar industrial composition, and seemingly fail to foster local specialisation-based economies. Highlights: Local agglomeration economies were identified in Hong Kong from 2000 to 2015. The main employment centres in Hong Kong exhibit strong location agglomeration. A few relatively small employment sub-centres are located in new town areas. New towns' employment sub-centres share homogeneous characteristics. Most new towns have not formed a substantial agglomeration economy.